Consistency between Musrenbang Results and Southeast Aceh District Government Work Plan (RKP) - Hendra Hendra; Erlina Erlina; Asfriyati Asfriyati (Budapest International Research and Critics University, 2020)
This research presents the latest information on the analysis of Islamic law on the practice of fulfilling the rights of wives and children in the household among the Tablighi Jama'ah. This research is presented in a qualitative form with the approach of sociology of law (Islamic law). This study uses Islamic law (mashlahat theory) as an analysis tool in analyzing research data. In the end, this study concluded that the rights and obligations of husband and wife and children in the household among the Tablighi Jama'ah were actually subject to and did not differ from the provisions of Law No. 1 of 1974, KHI and so from the opinion of Imam Shafi'i, although in reality related to the Tablighi Jama'ah policy, especially when selecting members who want to leave the khuruj still needs to be improved so that there are no more members of the jama'ah who are mentally incapable, especially financially making khuruj, so this does not impact on the non-implementation of the obligations of the husband in the household and the poor image of preaching khuruj in the midst of society, especially the city of Medan.